Entrepreneurial Intentions of Vocational College Students: The Role of Innovation Education and Initiative Personality - Yudhi Arifani; Qili Zhou (Al-Qalam Institute, 2026)
The rapid shift toward a knowledge-based economy highlights the importance of entrepreneurship and innovation in higher education. This study investigates how innovation and entrepreneurship education and students' initiative personality influence entrepreneurial intentions, while also examining the role of demographic characteristics such as age, gender, and family income. A quantitative survey was administered to 750 higher vocational college students, and the data were analyzed using descriptive statistics, t-tests, ANOVA, and multiple linear regression. Results indicate that both innovation and entrepreneurship education (β = 0.322, p < 0.01) and initiative personality (β = 0.559, p < 0.01) significantly and positively affect entrepreneurial intentions, with initiative personality having a more substantial effect. Demographic factors, including age, gender, and household income, also significantly differentiate entrepreneurial intentions. This study contributes by integrating educational and personality perspectives to explain entrepreneurial intentions in vocational students. Findings suggest that enhancing entrepreneurship curricula while fostering proactive traits can effectively strengthen students' entrepreneurial motivation and practical readiness.